Trip Companion Tour Together and Expense Tracker Application - Pravallika Bheemarasetty,; Dr. S. R. Raja, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Trip Companion is a comprehensive mobile application designed to enhance the experience of group travel by combining tour organization features with expense tracking functionalities. With the rising popularity of group travel, managing itineraries, coordinating activities, and tracking expenses can become overwhelming. Trip Companion aims to streamline these processes, ensuring a smooth and enjoyable journey for all travelers. The application offers a user-friendly interface accessible via mobile devices, allowing users to create and manage trips effortlessly.
Keywords: Visual Studio Code; Android Studio; MySQL; node JS; Flutter; React; AWS